HUBUNGAN ANTARA PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) OLEH MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR (PGSD) DENGAN KEMAMPUAN SELF-EFFICACY - Dwi Magfirah, Anugrah; Al Mukarramah, Salwa; Risdayanti; Aulia, Siti; Hanika, Zahnas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the correlation between Artificial Intelligence (AI) utilization among Elementary School Teacher Education (PGSD) students and their level of academic self-efficacy. A quantitative approach was employed using simple Pearson correlation analysis. The research involved 20 students as participants. Data collection was carried out through an online questionnaire based on a Likert scale ranging from 1 to 5, comprising 10 statement items, with the first 5 items measuring AI usage (X) and the remaining 5 items assessing self-efficacy (Y). Statistical analysis revealed a Pearson correlation coefficient of r = 0.859 with p < 0.001, confirming a highly significant and strong positive association between the intensity of AI use and the academic self-efficacy of PGSD students.